Mental health, duration of unemployment, and coping strategy: a cross-sectional study of unemployed migrant workers in eastern china during the economic crisis - Chen Li; Li Wenhu; He Jincai; Wu Lanhua; Yan Zheng; Tang Wenjie (BMC, 2012)
Abstract Background 20 million migrant workers in China lost their jobs during the economic crisis of 2008. Both urban migration and unemployment have long been documented to be associated with vulnerability to mental problems. This study aims to examine the mental health of unemployed migrant workers in Eastern China and its relation to duration of unemployment and coping strategy during the recent economic crisis. Methods The data were collected through interview-based survey with a sample of 210 unemployed migrant workers in Zhejiang Province of China from 2008 to 2009. Symptom Checklist-90-Revised, Coping Strategies Questionnaire, and seven short demographic questions were used. Results The majority of the unemployed migrant workers were found to be young male manufacturing industry workers with short-term unemployment and a relatively low education level. Nearly 50% of unemployed migrant workers were classified as mentally unhealthy and the most frequently reported symptom was depression. Compared with the adult norm of 1986, 2003, and 2007 in China, unemployed migrants had more mental problems. Long-term unemployed migrant workers had more psychiatric symptoms than the short-term unemployed workers and employed migrant workers. Unemployed migrant workers with immature coping strategies expressed significantly more psychiatric symptoms than those with mixed and mature coping strategies. Duration of unemployment and two coping strategies, problem-solving and self-blaming, predicted the mental problems of unemployed migrant workers. Conclusions The results indicated that mental health status of unemployed migrant workers in Eastern China was poorer than the national adult norm. More psychiatric symptoms are evidenced among unemployed migrant workers who lost their jobs for a long term and who had immature coping strategies. These findings can be used for prevention and intervention of mental illness among unemployed migrant workers.